Correlates of Affectual, Associational, and Functional Solidarity among Digitally Literate Adults - Ochoa, Josefina; Parinas, Sherwin; Yalong, Bernadette (Journal of Interdisciplinary Perspectives, 2024)
Positive interactions are key to social harmony. Challenges such as unmet needs and cultural mismatches hinder the solidarity necessary in the workplace. Integrating mindfulness, intergenerational solidarity, and relational-cultural theories can help address the need for positive interactions, fostering mutual appreciation and provision of concern, and ensuring needs are effectively met and opportunities seized. This quantitative study involved 279 digitally literate adults and utilized three sets of questionnaires to measure hypothesized correlations between needs attainment, opportunity capture, cultural contextualization, and affectual, associational, and functional solidarity. The findings revealed high mean values for all facets of solidarity: 3.99 for affectual, 3.60 for associational, and 3.61 for functional, explaining 23%, 14%, and 13% of the variance respectively. Significant correlations were observed among needs attainment (0.56), opportunity capture (0.50), cultural contextualization (0.51), and all facets of solidarity, with a probability of 0.001, supporting the hypotheses. The data found a highly acceptable level of affectual solidarity and moderately acceptable levels of associational and functional solidarity, supporting the idea of transitioning from self to others and then to the workplace. A society where needs are met, opportunities recognized, and culture contextualized would interact harmoniously, leading to increased productivity and solidarity. These findings suggest that personal and environmental factors are significantly correlated with solidarity, as the workforce is mindful, expresses mutual concern, and is sensitive to each other's needs. Implications for assessing solidarity in the workplace and providing learning support are discussed.